In Vitro Study of Calcium Hydroxide Microencapsulation with Stichopus hermanii as Pulp Capping Material - Rochyani, Linda; Sari, Rima Parwati; Rizal, Moh Basroni (Odonto : Dental Journal, 2025)
Background: Calcium hydroxide is a material that is widely used in pulp capping treatment. However, the use of this material causes tunnel defects due to the large absorption of calcium. This can be manipulated by creating an encapsulation formula. Stichopus hermanii is a marine biota that contains lots of hyaluronic acid and can be used as an encapsulation material which also plays a role in cell regeneration. The characteristics of the microencapsulated calcium hydroxide preparation with Stichopus hermanii as pulp capping material through an in vitro study.Method: Stichopus hermanii was made freeze dry and dissolved with 1% acetic acid to obtain a gel concentration of 0.2%, 0.4%, and 0.8%. Next, calcium hydroxide powder is added with a ratio of 1: 6 and tripolyphospate (TPP) is added as a cross-linker agent and the mixture is stirred until homogeneous. The test material formed was subjected to SEM, PSA and cytotoxicity tests.Result: The cytotoxicity test showed that all of the test materials (0.2%; 0.4%; 0.8%) were not toxic, especially at a concentration of 0.2%. The PSA test results indicate that this encapsulation shows the micro particle size formed. The SEM test shows a rough and stringy surface shape, where at a concentration of 0.2%, a smoother morphological formation is found.Conclusion: The in vitro study showed that the microencapsulation of calcium hydroxide with Stichopus hermanii as a pulp capping material showed the characteristics of the non-toxic material, the micro size and the rough and fibrous surface shape.